Process of tender for a project of ‘kerja-kerja pembaikan & baik pulih bangunan (Sivil & Elektrikal) serta kerja berkaitan termasuk pagar keselamatan di Kuarters Polis Wakaf Mek Zainab, Kota Bharu, Kelantan / Najihah Mahfuzah Mazlan - Mazlan, Najihah Mahfuzah (Universiti Teknologi MARA UiTM,Perak, 2022)
INB ENTERPRISE was established on 26th JUNE 2004. The history of this company was established due to deep interest in business, especially the construction and supply sector. This company is a BUMIPUTERA contractor company and conducts business in civil engineering and supply. The management of INB ENTERPRISE is led by experienced individuals and has trained and skilled employees. Educated in the field of Mechanical Engineering at Kota Bharu Polytechnic in 1996 to 1999, Mohd Harisan Bin Ya are as the manager of this company and has established INB ENTERPRISE to respond and plan development which the government wants. With the experience of Mohd Harisan Bin Ya have while working with a local company, he have applied for a construction contractor license. INB ENTERPRISE has obtained a license in class G1 with the Contractor Service Center (PKK) and registered with the Malaysian Construction Industry Development Board (CIDB). This company is also, has obtained a financial license from the Ministry of Finance Malaysia (MOF).